Emerging imaginaries of women's football - Díaz-Bajo Rodríguez, Javier; Martínez Borda, Rut; Infante Pineda, Sara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Social imaginaries are conceived as schemes that allow us to perceive something as real, explain it and intervene operationally in what contemporary societies consider to be reality. This work seeks to infer the social representations that emanate from the advertising strategies that were produced and disseminated by UEFA (Union of European Football Associations), as well as by its official sponsors, in the promotion of the women's football championship: UEFA Women's Euro 2022. The results demonstrate the social function that brands acquire when representing, legitimizing and promulgating a transnational and globalized vision of women in football and in society.